Peningkatan Nilai Keterampilan Shooting Bola Basket Peserta Didik Kelas VIII dengan Menerapkan Konsep Triple Threat - Farhan, Mohammad; Haris, Mochammad; Kristina, Irene Ika; M. Nukman I. K; Stiawan, Imron; Rofiq, M. Ainur; Sumardi; Rohmatul, Hadi Fajri (SPRINTER: Jurnal Ilmu Olahraga, 2025)
Physical Education, Sport and Health (PJOK) plays an important role in developing students' fitness, health, and cognitive, psychomotor and affective skills. However, in today's digital era, the decline in physical activity has an impact on the low level of fitness and student learning outcomes. This study aims to improve shooting skills in basketball games through the application of the triple threat concept in class VII students at SMP Negeri 32 Surabaya. This research uses a quantitative descriptive method with a one group pretest-posttest design. The sample consisted of 31 students and the instrument used was a shooting practice assessment sheet. Data analysis was carried out with descriptive statistical tests, normality tests, and paired sample t-test using SPSS 25. The results showed an increase in the average score from 54.19 in the pretest to 81.94 in the posttest, with a difference of 27.75 points. The paired sample t-test calculation shows a significance value of 0.000 (<0.05), which means there is a statistically significant increase. Thus, the application of the triple threat concept proves an effective increase in the learning outcomes of basketball shooting techniques in students.